Key Technologies of Magnetically-Coupled Resonant Wireless Power Transfer - Zhang, Yiming (Springer Theses, Recognizing Outstanding Ph.D. Research,, 2018)
This thesis focuses on the key technologies involved in magnetically coupled Wireless Power Transfer (WPT). Starting from the basic structures and theories of WPT, it addresses four fundamental aspects of these systems. Firstly, it analyzes the factors affecting transfer efficiency and compares various methods for reducing the working frequency. Secondly, it discusses frequency splitting and offers a physical explanation. Thirdly, it proposes and assesses three multiple-load transfer structures. Lastly, it investigates WPT systems with active voltage-source and current-source load. As such, the thesis offers readers a deeper understanding of WPT technology, while also proposing insightful new advances.